Pengembangan Pembelajaran Ilmu Pengetahuan Alam (IPA) Berbasis Learning Management System Schoology di SMK Muhammadiyah Delanggu - Ika Trisnawati, Septian Nur (Tahta Media Group, 2022)
Lack of optimized in using infrastructure and media to support a learning process is the basic of this research. The aims of the research is to understand the student’s learning result, develop and describe the effectiveness of Learning management system schoology as learning media in IPA (Science) subject in terms of student learning outcomes, in X grade of Business Management program SMK Muhammadiyah Delanggu. The methodology of this research is using Research and Development Method (RnD), with design learning model ADDIE (Analysis – Design – Development – Implementation – Evaluation).The try out of the research show indicated that Learning management system schoology media effective to increase score of student learning, it can be seen from the pretest average student learning value 44,85 become 88,79 in posttest with significance (α) 5% or 95% level of trust.